Effective School Plants Maintenance: Issues and Approaches in Nigerian Schools - Adamu, Bashir (NIU Journal of Social Sciences, 2019)
This paper examined the approaches for effective school maintenance in Nigerian schools. It is observed that most of the schools have been destroyed during the crises which had left most of school plant at varying level of dilapidations and for the fact that government alone cannot shoulder the responsibilities of school plant maintenance and provision. It is based on that that the paper x-rayed the concepts of school plants and the approaches that can be adopted by the educational managers to enhance effective school plant maintenance in their schools in Nigeria. Suggestion was also made for quality maintenance in Nigerian schools. Keywords: Approaches, School plant maintenance and schools.